Comprehensive Study of Technological Integration in General Healthcare Services and Retention and Burnout Solutions - Alhawsaw, Faizah Faez; Alghamdi, Ayed Said; Al-Mutairi, Abdullah Munif; Alomireen, Sali Hassan; Alanazi, Fatimah Abdullah; Alrizqi, Mohammed Ali Muidh; Alhaiz, Maryam Ali; Alsakran, Fatima Hussain; Alharthi, Alanoud Talal; Balhareth, Fatimah Mohmmed; Alanazi, Asma Humood; Alzhrani, Ghadah Ahmed (Journal of Ecohumanism, 2024)
This paper reviews the factors technology includes in healthcare provision and the issues of retention and burnout among healthcare workers. Technological developments like Artificial Intelligence (AI), Telemedicine, Electronic Health Records (EHRs), and Data analytics are helpful and effective change agents in delivering healthcare, enhancing patient care, and reducing complexities and costs. However, these have introduced new ethical issues like patient confidentiality and the need to acquire the workforce. On the same note, while providing care to COVID-19 patients, various healthcare personnel are overwhelmed by the many hours worked, stress, and demoralization by emotional work demands, among others. This paper will look into how the integration of technology has affected healthcare services, the causes of high retention problems/burnout, and strategies to walk out of these challenges, emphasizing how technology can lighten up the burden, work-life balance, and wellness of caregivers